The impact of ESG performance on the financial performance of companies: evidence from China's Shanghai and Shenzhen A-share listed companies - Zhang, Li-Sen (Frontiers in Environmental Science, 2025)
IntroductionCorporate ESG (Environmental, Social, and Governance) performance has become a key factor in achieving sustainable and healthy development, as well as enhancing financial performance. This study examines the impact of corporate ESG performance on financial performance in the Chinese market, providing empirical evidence for its influence and implications.MethodsUsing panel data from Chinese A-share listed companies on the Shanghai and Shenzhen stock exchanges from 2009 to 2022, this study employs econometric models to analyze the relationship between ESG performance and financial performance. Endogeneity and robustness tests are conducted to ensure result reliability. Additionally, moderating effects and heterogeneity analyses are performed to explore influencing factors.ResultsThe findings indicate that corporate ESG performance significantly enhances financial performance. This conclusion holds after accounting for endogeneity and robustness tests. Further analysis reveals that financing constraints positively moderate the ESG-financial performance relationship, whereas corporate innovation focus has a negative moderating effect. Heterogeneity analysis shows that the positive impact of ESG performance is more pronounced in enterprises located in eastern regions, state-owned enterprises, and high-pollution industries.DiscussionThis study provides empirical evidence from China, demonstrating the critical role of ESG in corporate financial performance. The results offer valuable insights for policymakers, investors, and corporate managers aiming to promote sustainable development and optimize investment strategies.